Ibn al-ʿArabī's Kitāb Fuṣūṣ al-Ḥikam wa-Khuṣūṣ al-Kalim : Edition Based on the Earliest Extant Manuscript - al-ʿArabī, Muḥyī l-Dīn Ibn, (Islamic Sources / Maṣādir Islāmiyya ;, 2025)
Although the exemplar of the Fuṣūṣ al-ḥikam has mysteriously disappeared shortly after its composition, the earliest copy in al-Qūnawī's hand has survived. Having been collated with the orginal, read in front of Ibn al-ʿArabī, and signed by him, it stands as the vetustissimus and optimus. This edition is established on its reading and is checked against ʿAfīfī's classic. Besides a fully vocalized text, it provides an appended facsimile of the manuscript. The introductory section is the first comprehensive study that tracks the whole story of the manuscript and attempts to identify possible scattered traces of the lost original. It reviews attitudes towards the text, as well as a century of scholarly research on it, and illustrates key concepts of the Master's doctrine to help contextualize the book contents.